Hungarian Monitoring, 24 July 1989 . [Magyar rádiófigyelő], 1989. július 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Bonn interior minister's warming on emigration of GDR citizens - Military budget debate in the US - Gorbachev on the Siberian miners' strike Domestic Affairs: - Rezső Nyers and Károly Grósz's visit to Moscow - Interim election results - Contradictions of the Hungarian social democrats - Association of Political Prisoners welcomes declaration of October 23 as national celebration - "I condemned many people to death" - Documentary program on Ferenc Vida, leading judge in Imre Nagy trial - Mrs. Erzsébet Vészi Nagy on the Imre Nagy Foundation - Claim to have discovered real grave of Sándor Petőfi in Barguzin, Siberia - Transylvanian minister László Tőkés on what it means to be Hungarian in Romania Economy: - Minister Hütter on Hungarian-American agricultural agreement - Hungarian Democratic Forum (MDF) representative on the land law - Hungarian Socialist Workers' Party (MSZMP) Political Administration Committee urges faster changes in economic policy Külpolitika: - A bonni belügyi miniszter figyelmeztetése az NDK-polgárok kivándorlásával kapcsolatban - A katonai költségvetés vitája az Egyesült Államokban - Gorbacsov a szibériai bányászsztrájkról Belpolitika: - Nyers Rezső és Grósz Károly moszkvai látogatása - Az időközi választások eredményei - A hazai szociáldemokrácia ellentmondásai - A Politikai Foglyok Szövetsége üdvözölné okt. 23-a nemzeti ünneppé nyilvánítását - "Nagyon sok embert halálra ítéltem" - Dokumentumműsor Vida Ferenccel, a Nagy Imre-per tanácsvezető bírájával - Vésziné Nagy Erzsébet a Nagy Imre Alapítványról - A szibériai Barguzínban állítólag valóban Petőfi Sándor sírját találták meg - Tőkés László erdélyi lelkész elmondja, mit jelent ma magyarnak lenni Romániában Gazdaság: - Hütter miniszter a magyar-amerikai mezőgazdasági szerződésről - A MDF képviselője a földtörvényről - Az MSZMP Politikai Intéző Bizottsága gyorsabb változásokat sürget a gazdaságpolitikában